Pemanfaatan Gim Edukatif “I Can Do” Sebagai Upaya Meningkatkan Literasi Selama Pandemi - Chris Setiawan Adi Putra; Aninditya Sri Nugraheni (Balai Bahasa Sumatera Utara, 2021)
The weakening level of literacy among schoolchildren has resulted in a slowing of the increase in literacy in Indonesia. The purpose of this research is to find out how effective a person is in utilizing electronic media such as the “I Can Do” game application, especially during the pandemic in order to increase literacy. The method used in this research is descriptive qualitative research which produces a statement that the educational game application